2016
DOI: 10.1080/01616412.2016.1188483
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of changes in cognitive function of young rats after various/different doses of whole brain irradiation

Abstract: More than 20 Gy of whole brain irradiation dose can cause significant cognitive dysfunction in young rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…In NLR, radiation-induced cognitive dysfunction was demonstrated by the decrease of exploration time in the novel location or decreased discrimination ratio. In Sun's research, dosage of 20 Gy/1 f and 30 Gy/1 f, but not 2 Gy/1 f and 10 Gy/1 f impaired recognition memory by decreasing the exploration time in the novel location [52]. However, in the series studies by Acharya on stem cell transplantation [47][48][49] and the research undertaken by Tome [53], a dosage of 10 Gy/1 f could decrease the exploration time in the novel location.…”
Section: Novel Object Recognition and Novel Location Recognitionmentioning
confidence: 95%
See 4 more Smart Citations
“…In NLR, radiation-induced cognitive dysfunction was demonstrated by the decrease of exploration time in the novel location or decreased discrimination ratio. In Sun's research, dosage of 20 Gy/1 f and 30 Gy/1 f, but not 2 Gy/1 f and 10 Gy/1 f impaired recognition memory by decreasing the exploration time in the novel location [52]. However, in the series studies by Acharya on stem cell transplantation [47][48][49] and the research undertaken by Tome [53], a dosage of 10 Gy/1 f could decrease the exploration time in the novel location.…”
Section: Novel Object Recognition and Novel Location Recognitionmentioning
confidence: 95%
“…However, the results of Roughton's research were the opposite by decreasing the total time in the center, which indicated that a dosage of 8 Gy/1 f increased the level of anxiety [16]. In addition, the research work undertaken by Zhang and Sun indicated that dosages of 2 Gy/1 f, 10 Gy/1 f, 20 Gy/1 f and 30 Gy/1 f had no effects on the level of anxiety by exerting no influence on the total time or distance spent in the center [35,52]. 33 Gy respectively) were used to induce impairment in cognition.…”
Section: Cognitive Tests To Evaluate Radiation-induced Cognitive Dysfmentioning
confidence: 96%
See 3 more Smart Citations